Efficacy of Exercise Management for Pain and Forward Head Posture in Cervical Spondylosis: A Randomized Controlled Trial - Hayat, Mariam Umer; Ashfaq , Anam; Hafiza Qurat-ul-Ain; Manzoor, Maria; Hanif, Kamran (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine exercise management for pain and forward head posture in patients with cervical spondylosis. Study Design: Randomized Control Trial (IRCT20230124057196N2). Place and Duration of Study: Physical therapy department of Water and Power Development Authority (WAPDA) Teaching Hospital, Lahore, Pakistan, from Jun to Dec 2023. Methodology: Sixty-eight diagnosed cervical spondylosis patients aged 40-60 years of age were included, randomly allocated into experimental and control groups, 34 in each group. The experimental group received cervical, postural, and shoulder dynamic exercises, while the control group received cervical and postural exercises for the 6th week. Measurement of clinical outcomes, pain via visual analog scale, and forward head posture via craniovertebral angle was taken at baseline and 6th week. Results: Analysis of 61 patients was conducted with 31 in experimental group and 30 in the control group. Mean age for the experimental and control groups was 52.26±5.98, 52.40±5.69 years respectively. Results showed that there was a statistically and clinically significant difference between the groups from baseline to 6th week in pain p≤0.001 and forward head posture p≤0.001, more reduction in pain and forward head posture were observed in the experimental group. Conclusion: Cervical isometric, postural corrective exercises with shoulder dynamic exercises (experimental group) have a positive effect on patients with cervical spondylosis on clinical outcomes, that was pain and forward head posture.